Game physics pearls - Bergen, Gino van den; Gregorius, Dirk (A.K. Peters, 2010)
Implementing physical simulations for real-time games is a complex task that requires a solid understanding of a wide range of concepts from the fields of mathematics, physics, and software engineering. This book is a gems-like collection of practical articles in the area of game physics. Each provides hands-on detail that can be used in practical applications. The chapters cover topics such as collision detection, particle-based simulations, constraint solving, and soft-body simulation. An introductory section provides the mathematical foundations and offers some background for the problems i.